Extracurricular Activities Influencing Academic Performance of Undergraduate Medical Students of Bangladesh: Teachers’ and Students’ Views (Bangladesh Journal of Medical Education, 2020)
This descriptive cross sectional study was conducted to identify the teachers’ & students’ views according to extracurricular activities influencing academic performance of undergraduate medical students. The study period was July 2017 to June 2018.The study was carried out among four phases of undergraduate medical students & teachers of basic science, para clinical & clinical subjects of four (04) government & four (04) non-government selected medical colleges of Dhaka & outside Dhaka. Medical colleges were selected purposively & convenience sampling technique was adopted for data collection. A self-administered semi-structured questionnaire using five points Likert scale were administered on 58 teachers & 1020 students to collect data & an interview schedule was used to conduct in-depth interviews with 15 medical teachers. Study revealed that according to views of the medical students, factors like drug addiction 922(90.6%) & student politics 835(82.0%) were negatively influencing academic performance of undergraduate medical students. On the other hand, factors like indoor-outdoor games 791(77.7%), cultural activities 611(60.0%) & social activities 658(64.7%) were positively influencing on their academic performance. Findings of the students’ views were consistent with the teachers’ views. In-depth interview of the teachers revealed that students should take part in extra-curricular activities alongside their study. But it should be in a balanced way so that they do not hamper their study. Teachers should encourage students to participate in extra-curricular activities. Study recommended that medical campus should be kept free from the unhealthy student politics. Study also recommended to prevent drug addiction, the parents should be aware & the college authority should have adequate monitoring in the student hostels & should strictly implement any measure if required.Bangladesh Journal of Medical Education Vol.11(1) 2020: 32-42